The promotion of cervical cancer progression by signal transducer and activator of transcription 1-induced up-regulation of lncRNA MEOX2-AS1 as a competing endogenous RNA through miR-143-3p/VDAC1 pathway. Issue 1 (1st January 2021) - Liu, Xiao-xing; Bao, Qi-xiu; Li, Yan-mei; Zhang, Yan-hua
ABSTRACT: Long non-coding RNAs (lncRNAs) are the new regulators and biomarkers for various tumors. However, in cervical cancer (CC), the potential roles of lncRNAs are not well characterized. This research aimed at exploring the roles of MEOX2 antisense RNA 1(MEOX2-AS1) in CC progression and the underlying mechanisms. The examination of MEOX2-AS1 levels in CC specimens and cell lines was conducted by RT-PCR. Loss-of-function experiments were performed for the assays of proliferation, migration, and invasion of CC cells after various treatments. Animal experiments were applied for the determination of the effects of MEOX2-AS1 in vivo. Bioinformatics analysis, together with dual-luciferase reporter assays, was applied to demonstrate the possible relationships among MEOX2-AS1, miR-143-3p and VDAC1. In the paper, we reported that MEOX2-AS1 levels were distinctly upregulated in CC cells and tissues, and higher MEOX2-AS1 expressions indicated a poor clinical outcome. Besides, STAT1 could activate transcriptions of MEOX2-AS1 by binding directly to its promoter region. The silence of MEOX2-AS1 suppressed the metastatic and proliferative ability of CC cells, as revealed by functional assays. Mechanistically, MEOX2-AS1 sponged miR-143-3p to regulate VDAC1 expressions. Furthermore, miR-143-3p inhibitor reversed the anti-proliferation and anti-metastasis effect of MEOX2-AS1 knockdown. Overall, the data indicated that the MEOX2-AS1/miR-143-3p/VDAC1 pathway participated in CC progression, making it a novel therapeutic target for CC cures. Graphical abstract: uf0001